1986
DOI: 10.1007/bf00493378
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y (NPY) immunoreactive neurons in the retina of different species

Abstract: Neurons displaying Neuropeptide Y (NPY) immunoreactivity were found among amacrine cells in the retina of baboon, pig, cat, pigeon, chicken, frog, trout, carp and goldfish. The immunoreactive cell bodies were located in the middle and the innermost cell rows of the inner nuclear layer with processes forming one, two or three more or less well-defined sublayers in the inner plexiform layer. The location and the density of the sublayers varied with the species investigated. In the frog retina, bipolar-like cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 20 publications
3
79
0
Order By: Relevance
“…3,4 NPY actions are mediated by G protein-coupled receptors, which have been named NPY Y 1 , Y 2 , Y 4 , Y 5 , and y 6 . 3,5 NPY is expressed in the retina of mammals and nonmammals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 NPY actions are mediated by G protein-coupled receptors, which have been named NPY Y 1 , Y 2 , Y 4 , Y 5 , and y 6 . 3,5 NPY is expressed in the retina of mammals and nonmammals.…”
Section: Resultsmentioning
confidence: 99%
“…3,5 NPY is expressed in the retina of mammals and nonmammals. [6][7][8][9][10][11][12] In rodent retinas, NPY-immunoreactivity (NPY-ir) is present in the inner retina, it is localized in cell bodies at both inner nuclear layer (INL) and ganglion cell layer (GCL), and is also present in processes located in the inner plexiform layer (IPL).11,13 NPY shows one of the highest degrees of phylogenetic preservation, compared with other neuropeptides, and does not show marked differences between species.14,16 From a consideration of the phylogenetic preservation, it is expected that the NPY and NPY receptor distribution in the retina does not vary significantly between species. NPY-ir is present in amacrine cells in the majority of species studied (fish, frogs, lizards, rodents, baboons, pigs, cats, chickens, and pigeons).…”
mentioning
confidence: 99%
“…Neuropeptide Y and its receptors are present in the retina of different mammalian and non-mammalian species (Bruun et al 1986;Jen et al 1994;Hutsler and Chalupa 1995;Oh et al 2002;D'Angelo and Brecha 2004). Moreover, some studies have demonstrated an early expression of NPY, suggesting that NPY may have a role in modulating the development of retinal circuitry (Ferriero and Sagar 1989;Jen et al 1994;Jotwani et al 1994;Bagnoli et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently described that NPY has a protective role against methamphetamine-induced neuronal apoptosis in the mouse striatum (Thiriet et al, 2005). NPY and its receptors are present in the retina of different mammalian and non-mammalian species (Bruun et al, 1986;Jen et al, 1994;Hutsler and Chalupa, 1995;Oh et al, 2002;D'Angelo and Brecha, 2004;Álvaro et al, 2007). Recently we showed that primary cell cultures of rat retinal neural cells express NPY and NPY receptors (Álvaro et al, 2007).…”
mentioning
confidence: 99%